Treatment of Late Class II Antibody-Mediated Rejection Status Postkidney Transplantation: Two Case Reports - Siskind, Eric; Bhaskaran, Madhu; Boctor, Fouad; Shah, Kavin; Molmenti, Ernesto (International Journal of Angiology, 2012)
We are describing the successful treatment of two cases of late Class II antibody mediated rejection status postkidney transplantation. The first patient was treated with a combination of plasmapheresis, intravenous immunoglobulin (IVIG), and stenting of the transplanted renal artery. The second was treated with IVIG and pulse steroids.
Keywords: immune system; kidney; renal disease; stent; transplant; angioplasty; artery